The Child’s Position in the Educational Situation and the Development of Coherent Speech - Veraksa, A.N.; Veraksa, N.E.; Oshchepkova, E.S.; Plotnikova, V.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The question of the child's position in the educational process is one of the controversial ones, since the answer to it determines the learning paradigm. The purpose of this study was to determine the influence of a child's position in an educational situation on the development of coherent speech. A randomized control experiment was conducted with the participation of 125 preschoolers (M = 70 месяцев, SD = 3,6, 50,4% male), final sample - 87 children. The children were divided into 5 groups: Play worlds, Free play, Research project, Creative Project and Control group. In two playgroups, which differed in the way of adult involvement, preschoolers acted in an imaginary situation and took a subject position. A creative situation was orginized in the project groups, but the author's position in Research group was much less than in Creative one. The participants of the Control group were in a typical of education system normative situation. As a result, children in Creative project showed the greatest number of significant or trend-significant positive effects and differences compared to other groups. Preschoolers in Play worlds also increased the scores of the macro and micro structures of narratives compared to the Control group. In the Free Play, there was a significant increase in scores in the macrostructure of the narrative compared to the Control group. In Research project the development of coherent speech was not recorded. The results obtained indicate the influence of the child's position on speech development and can be used for the practical implementation in preschool education. Вопрос о субъектности позиции ребенка в образовательном процессе является одним из дискуссионных, так как ответ на него определяет парадигму обучения. Целью данного исследования стало определение влияния степени субъектности позиции ребенка в образовательной ситуации на развитие связной речи. Был проведен слепой рандомизированный эксперимент с участием 125 дошкольников (M = 70 месяцев, SD = 3,6, 50,4% мальчиков), финальную выборку составили 87 детей. Дети были разделены на 5 групп: «Игровые миры», «Свободная игра», «Исследовательский проект», «Творческий проект» и контрольная группа. В двух игровых группах, отличавшихся степенью включения взрослого в игру, дошкольники действовали в мнимой ситуации и занимали субъектную позицию. В группах проектной деятельности создавалась творческая ситуация, но авторская позиция участников группы исследовательского проекта была значительно менее выраженной. Участники контрольной группы находились в типичной для образовательных учреждений нормативной ситуации и позиции ученика. Уровень связной речи оценивался с помощью методики MAIN. В результате в группе «Творческий проект» было зафиксировано наибольшее количество значимых или значимых на уровне тенденций положительных эффектов и различий с другими группами. Дети из группы «Игровые миры» показали значимое развитие макро- и микроструктуры нарративов по сравнению с контрольной группой. В группе «Свободная игра» зафиксирован значимый по сравнению с контрольной группой рост баллов по макроструктуре нарратива. В группе «Исследовательский проект» развитие связной речи не обнаружено. Полученные результаты свидетельствуют о влиянии степени субъектности позиции ребенка на речевое развитие и могут быть использованы для практической реализации в дошкольном образовании.